2001
DOI: 10.1053/rmed.2001.1070
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietic response to hypoxaemia in diffuse idiopathic pulmonary fibrosis, as opposed to chronic obstructive pulmonary disease

Abstract: The aim of this study was to assess the erythropoietic response to hypoxaemia in patients with diffuse idiopathic pulmonary fibrosis (DIPF), and to speculate on the underlying mechanisms. Patients on an established chronic respiratory failure due to DIPF or chronic obstructive pulmonary disease (COPD) were studied. The erythropoietic response to hypoxaemia in both conditions was assessed. We studied 18 patients with DIPF and 29 patients with COPD in respiratory failure in a stable stage, free from acute infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
25
1
7

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 20 publications
1
25
1
7
Order By: Relevance
“…2), which suggests that at least a component of the anemia is attributable to inflammation (ie, the anemia of chronic inflammation). 22 Tassiopoulos and colleagues, 23 in 2001, were among the first to study anemia and its compensatory erythropoietic action in COPD patients. Their findings indicated an inverse correlation between the hemoglobin and erythropoietin concentrations, which suggests that in COPD patients low hemoglobin correlates with a compensatory erythropoietin response.…”
Section: Pathophysiology Of Anemia In Copdmentioning
confidence: 99%
See 2 more Smart Citations
“…2), which suggests that at least a component of the anemia is attributable to inflammation (ie, the anemia of chronic inflammation). 22 Tassiopoulos and colleagues, 23 in 2001, were among the first to study anemia and its compensatory erythropoietic action in COPD patients. Their findings indicated an inverse correlation between the hemoglobin and erythropoietin concentrations, which suggests that in COPD patients low hemoglobin correlates with a compensatory erythropoietin response.…”
Section: Pathophysiology Of Anemia In Copdmentioning
confidence: 99%
“…27,28 The mechanism whereby inflammation causes anemia is incompletely established. However, cytokines such as the IL-1, IL-6, and tumor necrosis factor (TNF-alpha), released by activated monocytes in patients with underlying inflammatory conditions, 23,29 are certainly involved. Several studies have demonstrated that these and other cytokines are associated with the appearance of anemia and may be involved in the pathogenesis by mechanisms such as blunting erythropoietin production in response to hypoxia or decreasing bone marrow responsiveness to erythropoietin.…”
Section: Pathophysiology Of Anemia In Copdmentioning
confidence: 99%
See 1 more Smart Citation
“…S. Tassiopoulos и соавт. [19] одни из первых оценили связь АХЗ с ХОБЛ. Первоначальная цель состояла в сравнении компенсатор-ных механизмов эритропоэза у пациентов с идиопатическим фи-брозом легких и ХОБЛ.…”
unclassified
“…Однако результаты оказа-лись противоречивыми. У пациентов с ХОБЛ уровень гемоглоби-на был нормальным или сниженным, несмотря на высокие кон-центрации ЭПО в плазме [19]. Эти данные подтверждены резуль-татами другого исследования, в котором также обнаружены более высокие уровни СРБ и ИЛ-6 у больных ХОБЛ [10].…”
unclassified